The art of love: using arts engagement as a promoter of relational maintenance in couples with dementia - Griggs, Anna Katherine, author; Faw, Meara, advisor; Long, Ziyu, committee member; Malinin, Laura, committee member (Colorado State University. Libraries, 2019)
Previous communication scholarship has thoroughly examined the use of relational maintenance behaviors as outlined by Canary and Stafford (2003) on various types of relationships. These relational maintenance behaviors include openness, positivity, assurances, shared tasks, and networks (Canary & Stafford, 2003). However, little scholarship applying relational maintenance to contexts involving a life-altering illness exists, especially from the care partner's perspective. With the rising threat of Alzheimer's Disease and related diseases (ADRD), it is necessary to better understand how these behaviors might play into interactions between loved ones. Specifically, this research explores the use of relational maintenance behaviors between partners where one person has ADRD and the other is their primary care partner as they are involved in a participatory arts engagement workshop. Data collection involved video observation during the workshop sessions and follow-up phone calls with care partners about their experience after each session. Using thematic analysis, this study implicates that participants use relational maintenance regardless of their mental capacity and that the use of these behaviors creates tensions primarily for care partners to balance. The findings of this research encourage further exploration of the use of relational maintenance by people with a life-altering illness and their loved ones in order to understand the complicated communicative process associated with the immeasurable effects of a life-altering illness.
Keywords: dementia; relational maintenance; interpersonal relationships; art